Development of an extremely concentrated solar energy delivery system using silica optical fiber bundle for deployment of solar energy: Daylighting to photocatalytic wastewater treatment - Roy, Joy Sankar [UNESP]; Morency, Steeve; Dugas, Gabriel; Messaddeq, Younès [UNESP] (Elsevier, 2021)
The effective utilization of solar energy is a big challenge as global energy demand is increasing sharply. In this paper, we present the details of design of an extremely concentrated solar energy delivery system (ECoSEnDS) and its possible utilization in daylighting and sustainable wastewater treatment. The EcoSEnDS is made with double mirror based solar concentrator coupled with pure silica optical fiber bundle. This device is capable to deliver 96 suns concentrated sunlight in first stage of testing where efficiency of the primary mirror is 50%. This device can distribute light equivalent to 813 incandescent bulbs of 60 W or 149 LED bulbs of 15 W. Therefore, this device can be used as daylighting system in the building and underground car parking area. Using appropriate semiconductor nanophotocatalysts, this device can be used for sustainable rapid wastewater purification process. We have used BiVO4 nanoparticles for photocatalytic methylene blue degradation and the complete (100%) purification of methylene blue stained wastewater was achieved within one hour using only 7 suns concentrated sunlight. Therefore, the ECoSEnDS will open new technological aspects for sustainable fastest wastewater treatment process using solar energy.
Keywords: Daylighting; Optical fiber; Photocatalysis; Solar concentrator; Solar energy; Wastewater treatment